Acholeplasma laidlawii PG8 Culture Adapted to Unfavorable Growth Conditions Shows an Expressed Phytopathogenicity - Vladislav M. Chernov; Natalia E. Moukhametshina; Yurii V. Gogolev; Tatiana N. Nesterova; Maxim V. Trushin; Olga A. Chernova (The Scientific World Journal)
Mycoplasmas are the smallest, self-replicating, prokaryotic organisms with avid biochemical potential and spreading in higher eukaryotes in nature. In this study, Acholeplasma laidlawii PG8 cells were cultivated on a deficient medium for 480 days resulting in a mycoplasma culture that was adapted in vitro to unfavorable growth conditions. Cells that survive this condition had decreased sizes (about 0.2 μm) and increased phytopathogenicity. This resulted in more frequent appearance of various morphological alterations when plants of vinca (Vinca minor L.) were infected by adapted mycoplasma cells. The increasing pathogenicity was accompanied by changes in genome expression in these adapted cells. Further studies are needed to explore the exact mechanisms that permit adaptation to unfavorable growth conditions and changes in phytopathogenic potential.